Elbow Grease vs. Motozilla - Cena, John; McWilliam, Howard, 1977- (New York : Random House, 2019)
Elbow Grease is back and about to face off against the gnarly monster machine Motozilla, but it's going to take teamwork. Luckily, Elbow Grease can count on his four big brothers to rev their engines and help him try to beat the beast!
Keywords: Monster trucks -- Juvenile fiction; Trucks -- Juvenile fiction